(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
A girl is at risk of being a victim or target of crime from the moment she is born, if not sooner.Let’s examine the potential dangers at different times in a woman’s life. The kind of crimes also differsamong phases. Important points are shown in the tables and diagrams that follow. According to the 2012report by India’s National Crime Records Bureau, the country’s overall crime rate was 46 per 100,000people, the rape rate was 2, the dowry homicide rate was 0.7, and the domestic cruelty rate was 5.9 per100,000. It is estimated that 27.5 million women in India are victims of sexual assault, despite the fact thatIndia has one of the lowest rates of sexual violence in the world (8.5). The 2006 study also indicatedthat just 1 of victims of sexual assault in relationships or outside of marriage ever go to the police foraid. Through this work, the researcher has made an effort to discuss the topic of crimes against womenin the present day. Crimes committed against women in India are the primary topic of this study. Thereare a variety of ways in which women in India are confined. There is no one demographic that isdisproportionately affected by crime. Indian women have always had trouble with their periods, not justnow. Despite several laws and other government initiatives, the rate of violence against women has notdecreased.